Investigation of CVD multilayered graphene as negative electrode for lithium-ion batteries. (1st August 2017) - Saulnier, Mathieu; Trudeau, Charles; Cloutier, Sylvain G.; Schougaard, Steen B.
Highlights: Multilayered graphene film fabricated by chemical vapor deposition for Li-batteries. Systematic analysis of deposition time and temperature effects. Argon plasma treatment to improve performance. Electrochemical performance correlated to morphology, chemical and crystal structure. Abstract: Multilayered graphene (MLG) grown by chemical vapor deposition (CVD) was examined as a negative electrode for lithium-ion batteries. Experimental parameters such as deposition time and temperature were examined to produce carbon loadings between 0.06–0.17 mg cm −2 and film thicknesses in the 1 μm range. The MLG thin films obtained on nickel substrate were used without conductive additive and binding agent in electrochemical tests to produce a capacity of ∼250 mAh.g −1 at the 5C rate. Films were further characterized by scanning electron microscopy, atomic force microscopy, grazing angle X-ray diffraction, X-ray photoelectron spectroscopy and Raman micro-spectroscopy mapping. By correlating the structural analysis to the electrochemical properties the importance of edge plane accessibility is emphasized. Separately, a pre and a post deposition treatment were used to improve the electrochemical performances, validating the structural performance limitation hypothesis. In particular, the use of argon plasma post treatment yielded major improvement of the electrochemical performance, which was ascribed to enhanced crystallite edge accessibility.